EVOLUTIVE COMPUTING AND GAMES THEORY: A HIBRID FOR THE AUTOMATIZATION IN BUSINESS SUPPORT SYSTEMS - Velez-Langs, Oswaldo (2006)
This paper is about the decisión analysis methods for group decisions over the web, in reason of involve the people in the different decisions that interest them, we have in internet one chance for to reduce the gap between governor and governed We can summarize the main object that pursues this like to propose one automated negotiation approach in the web, which be based on the evolutionary computation and the game theory.